2014
DOI: 10.1159/000362744
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sustained Arteriovenous Access Use for Haemodialysis

Abstract: Background: Guidelines encourage early arteriovenous (AV) fistula (AVF) planning for haemodialysis (HD). The aim of this study was to estimate the likelihood of sustained AV access use taking into account age, sex, comorbidity, anatomical site of first AVF and, for pre-dialysis patients, eGFR and proteinuria. Methods: 1,092 patients attending our centre who had AVF as their first AV access procedure between January 1, 2000 and August 23, 2012 were identified from the electronic patient record. The primary end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Additionally, one of the three studies included in the 6 month rate analysis only included patients that had one previously failed access, 17 and another included a unique maturation definition. 16 Clarity of reporting is paramount to understanding the true value of AVF as an access modality. The challenges of inconsistent or unclear outcomes terminology underscore the importance of applying a consistent set of definitions and nomenclature for specific fields.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one of the three studies included in the 6 month rate analysis only included patients that had one previously failed access, 17 and another included a unique maturation definition. 16 Clarity of reporting is paramount to understanding the true value of AVF as an access modality. The challenges of inconsistent or unclear outcomes terminology underscore the importance of applying a consistent set of definitions and nomenclature for specific fields.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated clinical predictors of FTM with no general consensus [ 15 , 19 21 ]. In our population of 525 patients, female gender and lower-arm AVF site were the only predictors of AVF FTM.…”
Section: Discussionmentioning
confidence: 99%
“…Variables with p < 0.10 in unadjusted analysis were introduced into multivariate analysis as covariates because of the possibility of negative confounding. Also, our model development used 'forced' entry to account for factors known to be clinically associated with the outcome variable, based on existing literature [8,26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Because AVF require several weeks to mature and approximately 40% of created AVF never mature [4] , AVF creation is reliant on predialysis care, especially predialysis nephrology referral [5][6][7] . While studies of the development and maturation of AVF have focused on clinical factors [8][9][10][11] , the role of socioeconomic factors, particularly individual-level poverty, has not been reported in a recent national cohort of dialysis patients, although a previous study reported that county-level poverty was inversely associated with incident AVF use, but not with subsequent improvement in AVF use in prevalent patients [12] . We have previously reported that AVF use in new HD patients is significantly higher among patients in the federal health system (e.g.…”
Section: Impact Of Poverty and Healthmentioning
confidence: 98%